Chronic DDE Exposure Modifies Mitochondrial Respiration during Differentiation of Human Adipose-Derived Mesenchymal Stem Cells into Mature Adipocytes - Kladnicka, Iva; Cedikova, Miroslava; Jedlicka, Jan; Kohoutova, Michaela; Muller, Ludek; Plavinová, Iveta; Kripnerova, Michaela; Bludovska, Monika; Kuncova, Jitka; Mullerova, Dana (Biomolecules, 2021)
The contribution of environmental pollutants to the obesity pandemic is still not yet fully recognized. Elucidating possible cellular and molecular mechanisms of their effects is of high importance. Our study aimed to evaluate the effect of chronic, 21-day-long, 2,2-bis (4-chlorophenyl)-1,1-dichlorethylenedichlorodiphenyldichloroethylene (p,p'-DDE) exposure of human adipose-derived mesenchymal stem cells committed to adipogenesis on mitochondrial oxygen consumption on days 4, 10, and 21. In addition, the mitochondrial membrane potential (MMP), the quality of the mitochondrial network, and lipid accumulation in maturing cells were evaluated. Compared to control differentiating adipocytes, exposure to p,p'-DDE at 1 μM concentration significantly increased basal (routine) mitochondrial respiration, ATP-linked oxygen consumption and MMP of intact cells on day 21 of adipogenesis. In contrast, higher pollutant concentration seemed to slow down the gradual increase in ATP-linked oxygen consumption typical for normal adipogenesis. Organochlorine p,p'-DDE did not alter citrate synthase activity. In conclusion, in vitro 1 μM p,p'-DDE corresponding to human exposure is able to increase the mitochondrial respiration per individual mitochondrion at the end of adipocyte maturation. Our data reveal that long-lasting exposure to p,p'-DDE could interfere with the metabolic programming of mature adipocytes.
Keywords: Mitochondria; adipogeneze; Obesity; Dichlorodiphenyl Dichloroethylene; látky znečišťující životní prostředí; buněčná diferenciace; obezita; Adipocytes; kultivované buňky; tukové buňky; lidé; ženské pohlaví; Adipogenesis; Humans; Environmental Pollutants; membránový potenciál mitochondrií; Cells, Cultured; dichlordifenyldichlorethylen; Female; Mesenchymal Stem Cells; Membrane Potential, Mitochondrial; mitochondrie; Cell Differentiation; mezenchymální kmenové buňky